Plurilingual and Pluricultural Practices in Turkish Study Abroad: The Intersection of Identity and Lx Community - Brown, Bianca (Comparative and International Education / Éducation comparée et internationale, 2024)
Whereas second language acquisition has embraced the multilingual turn, study abroad (SA) research often assumes that learners are situated in monolingual host societies. As the profile and preferences of the sojourner diversify, destination sites become more cosmopolitan, and global migration patterns change the demographic makeup of communities, traditional models are no longer representative of SA. This article presents Turkish SA learners’ perceptions and experience of plurilingual and pluricultural practices. Through analysis of weekly journals, these practices are examined as a potential resource and constraint. Findings confirm the centrality of awareness in plurilingual practice, and shed further light on how plurilingual and pluricultural identity can support target language (TL) interaction more than seeking out “native speakers.” This study offers a unique contribution to the link between identity and language learning in SA, providing further support for the need to dismantle the preeminence of the “native speaker” as the target interlocutor in study abroad.